Immobilization of invertase on functionalized mesoporous silica and properties of the immobilized biocatalyst - Prabhune, Asmita Ashutosh; Sulabha, Karandikar; Archana, Pundle; Shilpa, Deshpande; Sanjeevani, Pardhy (Research Journal of Biotechnology, 2007)
Invertase, which catalyses the hydrolysis of sucrose, is one of the simplest commercial carbohydrases and is used for the production of invert syrup (mixture of glucose and fructose). Fructose is the sweetest natural sugar having beneficial medicinal effects and is emerging as an alternative sweetener to sucrose in the pharmaceutical industry. beta fructofuranosidase (E C 3.2.1.26) purified from Kluyveromyces marxianus NCYC 2675, a thermotolerant yeast, was immobilized on functionalized mesoporous silica SBA- 15. Attempts were made to immobilize invertase on functionalized silicalite and cross linked with glutaraldehyde so as to obtain a highly active and stable immobilized enzyme preparation suitable for commercial exploitation. Cross linked enzyme silica complex as well as enzyme silica complex showed very good temperature and pH stability. Extrudates of the mesoporous silica also showed similar results. Bound enzyme showed excellent stability to repeated use and retained 90% of its initial activity after ten cycles of reuse in batch mode.
Keywords: beta fructofuranosidase; extrudates; functionalized mesoporous silica; Invert syrup; invertase; SBA-15

Characterization of the smallest dimeric bile salt hydrolase from a thermophile brevibacillus sp. - Sridevi, N.; Srivastava, Sameer; Khan, Bashir Mohammad; Prabhune, Asmita Ashutosh (Extremophiles, 2009)
A thermophilic microorganism producing bile salt hydrolase was isolated from hot water springs, Pali, Maharashtra, India. This microorganism was identified as Brevibacillus sp. by 16S rDNA sequencing. Bile salt hydrolase (BSH) was purified to homogeneity from this thermophilic source using Q-sepharose chromatography and its enzymatic properties were characterized. The subunit molecular mass of the purified enzyme was estimated to be 28 kDa by SDS-PAGE and, 28.2 kDa by MALDI-TOF analysis. The native molecular mass was estimated to be 56 kDa by gel filtration chromatography, indicating the protein to be a homodimer. The pH and temperature optimum for the enzyme catalysis were 9.0 and 60A degrees C, respectively. Even though BSH from Brevibacillus sp. hydrolyzed all of the six major human bile salts, the enzyme preferred glycine conjugated substrates with apparent K (M) and k (cat) values of 3.08 mu M and 6.32 x 10(2) s(-1), respectively, for glycodeoxycholic acid. The NH2-terminal sequence of the purified enzyme was determined and it did not show any homology with other bacterial bile salt hydrolases. To our knowledge, this is the first report describing the purification of BSH to homogeneity from a thermophilic source.
Keywords: Bile salt hydrolase; Brevibacillus sp.; Dimeric intracellular enzyme; Purification; Thermophile

Microbial oxidation of medium chain fatty alcohol in the synthesis of sophorolipids by candida bombicola and its physicochemical characterization - Pulate, Vrushali Dengle; Bhagwat, Sunil S.; Prabhune, Asmita Ashutosh (Journal of Surfactants and Detergents, 2013)
Sophorolipids (SL) are glycolipid biosurfactants abundantly produced from different feedstocks by yeasts and have been widely developed for various applications. The amphipathic structures of sophorolipids imparts to them surfactant type properties. These biosurfactants are readily isolated in high yield and are nontoxic and biodegradable, which make them industrially interesting as surfactants or emulsifiers. Sophorolipid production was carried out using glucose as a hydrophilic source and lauryl alcohol C12-14, as a hydrophobic source by Candida bombicola (ATCC 22214). Process economics and environmental attractiveness was increased by using a low cost substrate. Optimization studies were carried out where the effect of glucose concentration, pH, temperature and metal ions on sophorolipid production was studied. Optimum production of sophorolipid obtained using lauryl alcohol (SLLA) was achieved after 96 h, the initial pH of the medium was 6.0 with 10 % glucose at 30 A degrees C. Primary characterization of SLLA was done by FTIR. The SLLA showed high physicochemical properties in terms of the surface activities when compared with synthetic surfactants including dodecyl tetraethylene glycol ether and sodium lauryl sulfate. The surface tension of SLLA thus obtained was found to be 24 mN/m with a critical micellar concentration (CMC) value of 0.68 mg/L. Antimicrobial testing showed that SLLA have potent antimicrobial activity against both gram negative bacteria, Escherichia coli (ATCC 8739) and gram positive cocci, Staphylococcus aureuss (ATCC 2079).
Keywords: Biosurfactants; Candida bombicola; CMC; Lauryl alcohol C12-14; sophorolipids; Surface tension

Antimicrobial and SEM studies of sophorolipids synthesized using lauryl alcohol - Dengle-Pulate, Vrushali; Chandorkar, Parul; Bhagwat, Sunil S.; Prabhune, Asmita Ashutosh (Journal of Surfactants and Detergents, 2014)
In recent years, researchers have developed biosurfactants for industrial, pharmaceutical and medical applications revealing the promising biological activities of these biomolecules. One of the best studied microbial surfactants are glycolipids, especially sophorolipids (SLs) produced by selected non-pathogenic yeast species of Candida. They are biodegradable, non-toxic and are environmentally friendly. Sophorolipid production was carried out using glucose as the hydrophilic source and lauryl alcohol C12-14, as the hydrophobic source using Candida bombicola ATCC 22214. Primary characterization of the SL obtained using lauryl alcohol (SLLA) was done by FTIR which depicted the presence of alkyl sophorosides/SLs. Antimicrobial activity testing revealed that SLLA showed complete inhibition against gram negative bacteria, Escherichia coli (ATCC 8739) Pseudomonas aeruginosa (ATCC 9027) at 30 and 1 mu g/ml at a contact time of 2 and 4 h respectively. Whereas for gram positive bacteria Staphylococcus aureus (ATCC 6358), Bacillus subtilis (ATCC 6633), complete inhibition was observed at 6 and 1 mu g/ml respectively at a contact time of 4 h. The formed SLLA showed noteworthy inhibition against the pathogenic yeast Candida albicans (ATCC 2091) at 50 mu g/ml with a contact time of 4 h. These values are remarkably low compared to reported values of oleic acid SLs and linolenic acid SLs which were studied for antimicrobial properties. Scanning electron microscopy analysis of the treated cells revealed the changes in morphology and topography of the microorganisms.
Keywords: Antimicrobial property; Biosurfactants; Candida bombicola; Lauryl alcohol; sophorolipids

Diverse profiles of N-acyl-homoserine lactones in biofilm forming isolates of Cronobacter sakazakii - Singh, Niharika; Patil, Amrita; Prabhune, Asmita Ashutosh; Raghav, Mamta; Goel, Gunjan (Virulence, 2017)
The present study investigates the role of quorum sensing (QS) molecules expressed by C. sakazakii in biofilm formation and extracellular polysaccharide expression. The QS signaling was detected using Chromobacterium violaceum 026 and Agrobacterium tumefaciens NTL4(pZLR4) based bioassay. Long chain N-acyl-homoserine lactones (AHLs) with C6- C18 chain length were identified using High Performance Liquid Chromatography and Liquid Chromatography-High Resolution Mass Spectrometry. A higher Specific Biofilm Formation (SBF) index (p < 0.05) with the presence of genes associated with cellulose biosynthesis (bcsA, bcsC and bcsG) was observed in the strains. AHLs and their mechanisms can serve as novel targets for developing technologies to eradicate and prevent biofilm formation by C. sakazakii.

Silk degumming and utilization of silk sericin by hydrolysis using alkaline protease from beauveria Sp. (MTCC 5184): a green approach - More, Snehal V.; Chavan, Sakalya; Prabhune, Asmita Ashutosh (Journal of Natural Fibers, 2017)
Conventionally, degumming is carried out at 90°C--110°C temperature by boiling the raw silk with Marseilles soap and sodium bicarbonate which eventually requires a lot of water and energy. In this study, degumming of Chinese bivoltine raw silk fibres with alkaline protease produced by Beauveria sp. (MTCC 5184) is studied. Complete degumming was obtained in 45 min with 75 units of enzyme per gram of silk. Degumming was found to be optimal at 50°C and pH 9.0. Scanning electron micrographs showed that the sericin deposits were removed and the obtained fibres were clean, separated, had smooth feel with shine as compared to untreated fibres. Sericin isolated from silk cocoon (by-product which goes waste) was hydrolyzed with the same alkaline protease obtained from Beauveria sp. to get small molecular weight peptides. These peptides can be utilized further for cosmetic, pharmaceutical, and various industrial applications.
Keywords: Alkaline Protease; bivoltine; degumming; Silk; weight loss